Correlation of microdistortions with misfit volumes in High Entropy Alloys. (15th July 2019) - Nöhring, Wolfram Georg; Curtin, W.A.
Abstract: The yield strengths of High Entropy Alloys have recently been correlated with measured or computed picometer-scale atomic distortions. Here, the root mean square microdistortion in a multicomponent alloy is shown to be nearly proportional to the misfit-volume parameter that enters into a predictive model of solute strengthening. Analysis of two model ternary alloy families, face-centered cubic Cr-Fe-Ni and body-centered cubic Nb-Mo-V, demonstrates the correlation over a wide composition space. The reported correlation of yield strength with microdistortion is thus a consequence of the correlation between microdistortion and misfit parameter and the derived dependence of yield strength on the misfit parameter. Graphical Abstract: Unlabelled Image